Spreading Dayflower Biology and Management in Turf - J. Bryan Unruh; Darcy E. P. Telenko; Barry J. Brecke; Ramon Leon (EDIS)
Spreading dayflower (Commelina diffusa) is a succulent annual that produces freely branched smooth stems. Leaves are broadly lance-shaped with closed sheaths. Sheaths are short with a few soft hairs on the upper margin. Flowers have three blue petals in a leaf-like structure open on the margins. Reproduction occurs via seed and stem fragments. This 2-page fact sheet was written by J. Bryan Unruh, Darcy E. P. Telenko, Barry J. Brecke, and Ramon Leon, and published by the UF Department of Environmental Horticulture, December 2013.